Potential of epigenetic therapies in non-cancerous conditions - Mau, Theresa; Yung, Raymond (Frontiers in Genetics, 2014)
There has been an explosion of knowledge in the epigenetics field in the past 20 years. The first epigenetic therapies have arrived in the clinic for cancer treatments. In contrast, much of the promise of epigenetic therapies for non-cancerous conditions remains in the laboratories. The current review will focus on the recent progress that has been made in understanding the pathogenic role of epigenetics in immune and inflammatory conditions, and how the knowledge may provide much needed new therapeutic targets for many autoimmune diseases. Dietary factors are increasingly recognized as potential modifiers of epigenetic marks that can influence health and diseases across generations. The current epigenomics revolution will almost certainly complement the explosion of personal genetics medicine to help guide treatment decisions and disease risk stratification.